Pengaruh Harga, Citra Merek, dan Kualitas Produk terhadap Keputusan Pembelian pada Chatime Kota Semarang - Syafagita, Oca Safura; Santoso, Agus Budi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Nowadays, there is a lot of competition in the food and beverage industry that has developed in Indonesia. Judging from the increasing demand and interest in beverage products among the general public. Businesses in the beverage industry are of great interest to business people. Chatime is one of the pioneers of bubble tea drinks in Indonesia which originates from Taiwan. The purpose of this research is to determine the influence of price, brand image and product quality on Chatime Semarang City. This research uses descriptive analysis and quantitative analysis. The data used is primary data with a questionnaire collection method. Data analysis using multiple linear regression analysis. The sample used was 100 respondents. The research results found that there was a positive and significant influence on the price variable on purchasing decisions, and likewise on the product quality variable. Meanwhile, the brand image variable does not have a significant effect.